The Role of Parents in Improving Children's Pedagogical Aspects of Online Learning: A Sociological Study - Lasmaria Nami Simanungkalit; Iham Arief; Pipit Aprilia Susanti; Irwandi Irwandi (HK-Publishing, 2022)
AbstractThis paper reveals the role of parents in their children's learning through systems in the network in a covid pandemic 19. The purpose of this study is that the purpose of this study is to determine what roles and contributions have been made and can be done when their children carry out online learning activities. In addition, this research can also describe what is being faced by parents in the midst of a covid-19 pandemic in accompanying their children. The approach and method used in this study uses a qualitative approach with descriptive methods. The findings obtained include the fact that parents face directly when accompanying their children to implement a learning system in the network, the child's response in learning in the network and the analysis of researchers using the theory of sociology. This study concludes the family in mentoring online learning in the covid-19 pandemic as the main spearhead in carrying out a role in encouraging children's enthusiasm for learning.Keywords: Roles, Parents, Online Learning,Technology, Covid 19, Education. AbstrakTulisan ini mengungkap peran orang tua dalam pembelajaran anaknya melalui sistem dalam jaringan di masa pandemi covid 19. Tujuan penelitian ini adalah untuk mengetahui peran dan kontribusi apa saja yang telah dilakukan dan dapat dilakukan ketika anak anak-anak melakukan kegiatan belajar online. Selain itu, penelitian ini juga dapat mendeskripsikan apa yang sedang dihadapi orang tua di tengah pandemi covid-19 dalam mendampingi anaknya. Pendekatan dan metode yang digunakan dalam penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Temuan yang diperoleh antara lain fakta bahwa orang tua berhadapan langsung saat mendampingi anaknya menerapkan sistem pembelajaran dalam jaringan, respon anak dalam pembelajaran dalam jaringan dan analisis peneliti menggunakan teori sosiologi. Penelitian ini menyimpulkan keluarga dalam pendampingan pembelajaran online di masa pandemi covid-19 sebagai ujung tombak utama dalam menjalankan peran dalam mendorong semangat belajar anak.Kata kunci: Peran, Orang Tua, Pembelajaran Daring, Teknologi, Covid 19, Pendidikan.